Implementasi Gerakan Literasi Sekolah dalam Menumbuhkan Minat Membaca dan Menulis Pada Pembelajaran PAI - Achmat Mubarok; Syafa’atul Islamia (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2022)
Education is basically to form and create quality human resources, but the problem that exists in the world of education is the low quality of education at every level and unit of education. So in this world of education the importance of literacy as an effort to build a generation of people with broad insight and virtuous character. The purpose of this study was to determine the various kinds of school literacy programs in fostering interest in reading and writing in students. To answer various problems how to implement, and what are the population factors and share barriers to the implementation of the school literacy movement at SDN Baujeng 1. The approach used is descriptive qualitative method. The results showed that implementation was realized through the implementation of reading activities, the supporting factor was the active role of students and the inhibiting factor, namely: the condition of the book that was not feasible. The solution to overcome the implementation problem is to create a reading study group and provide proper facilities, as well as provide a reading corner room, providing motivation to students at SDN Baujeng 1.